Quantity and quality of household wastewater in Kuching, Sarawak - Ling, Teck Yee; Lee, Nyanti; Siew, Tuck-Fatt (Proceedings of the International Conference on Natural Resources and Environmental Management 2005, 2005)
In Kuching City, individual septic tank is the most common form of sewerage system for most of the residential areas whereby effluents are discharged into municipal storm drains. However, little is known about the contribution of household wastewater towards river water quality degradation. In this study, key pollutant concentrations and loadings were investigated during the dry season at two housing areas. Results indicated that mean per capita wastewater flowrate (82.5 l/c/d) was about one third of the water consumption rate (222.1 l/c/d). Dissolved oxygen concentration ranged from 1.38 to 4.22 mg/l. Mean pollutant loadings of BOD5, phosphate, and nitrate were found to be 1,825 mg/c/d, 519 mg/c/d, and 3.3 mg/c/d respectively. With the population of 35, 750 from the two housing areas, it is estimated that the mean daily contribution of BOD5, phosphate, and nitrate are 62.9 kg, 18.8 kg and 115 g respectively. In order to minimize pollution, it is recommended that pollution control at source be implemented.